Analysis of m6A-Related Signatures in the Tumor Immune Microenvironment and Identification of Clinical Prognostic Regulators in Adrenocortical Carcinoma - Jin, Yi; Wang, Zhanwang; He, Dong; Zhu, Yuxing; Hu, Xueying; Gong, Lian; Xiao, Mengqing; Chen, Xingyu; Cheng, Yaxin; Cao, Ke (Frontiers in Immunology, 2021)
Adrenocortical carcinoma (ACC) is a rare endocrine malignancy with high rate of mortality and recurrence. N6-methyladenosine methylation (m6A) is the most common modification to effect the development of cancer, but so far, the potential role of m6A regulators in ACC prognosis is little known about. In this study, we systematically analyzed 21 m6A regulators in ACC samples from The Cancer Genome Atlas (TCGA) and The Gene Expression Omnibus Database (GEO). We identified three m6A modification patterns with different clinical outcomes and discovered significant relationship between diverse m6A clusters and tumor immune microenvironment (immune cell types, ESTIMATE algorithm). Additionally, the GO, KEGG, and GSEA analysis also revealed that the m6A clusters was intensively associated to immune infiltration in ACC. Next, for further explore the m6A prognostic signatures in ACC, we implemented LASSO Cox regression to establish an eight-m6A-regulator prognostic model in the TCGA dataset and the results displayed that model-based high-risk group was closely correlated with poor the overall survival (OS) compared to low-risk group. Subsequently, we validated the key modifications in the GEO datasets and found that high expression of HNRNPA2B1 showed poor OS and the event-free survival (EFS) in ACC. Moreover, for further decipher the molecular mechanisms, we constructed a competing endogenous RNA (ceRNA) network based on HNRNPA2B1 which consist of twelve lncRNAs and one mirRNA. In conclusion, our finding indicated the potential role of m6A modification in ACC, providing novel insight into ACC prognosis and guide of immunotherapy.